The role of surface proteins in cell proliferation as studied with thrombin and other proteases. - Teng, N N (1975)
This communication explores the capacity of different proteases to stimulate DNA synthesis in resting chick embryo fibroblasts and to cause the removal of cell membrane proteins previosly postulated as important in the regulation of growth and division of cells. Thrombin, a highly specific protease and a known mitogen, was incubated with chick embryo fibroblasts, and analysis was made of the cell membrane proteins. Of particular interest were a protein of molecular weight 250,000, which is known to be readily removed by the action of trypsin and is not present in most transformed cells, and two other proteins, which are reduced in amount in transformed as compared to confluent resting cell cultures. None of these three proteins was removed by thrombin when the latter was added to confluent cells in concentrations sufficient to cause significant increase in DNA synthesis twelve hours after stimulation by the protease. The presence or absence of these proteins in the membranes of confluent resting or transformed cells of chick embryo fibroblasts does not seem to be directly related to the process of regulation of DNA synthesis and cellular division.